Сравнительный анализ планарной и пространственной аксиальной трёхфазных электромагнитных систем с параллельными образующими поверхностями стержней и обмоточных окон (массостоимостные показатели) - Авдеева, Е.А. (Електротехніка і електромеханіка, 2012)
Analytical dependences of optimum geometrical relationship
determination with criteria of minimal weight and price of the
active part are obtained. Comparative analysis of mass and price
indexes of planar and spatial three-phase electromagnetic systems
with rectangular and sector forming contours of the cores,
yokes and winding coils is made.